LEGISLATIVE BASES OF ACCOUNTING OF EMPLOYEE COMPENSATIONS - A. Samartseva; Z. Сhebotareva (Вестник университета)
In this article considered legal regulation and documentation of accounting of employee compensations in the Russian practice, wage systems and order the deduction of tax on private income and insurance payments.